2020
DOI: 10.3390/ijms21061983
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor in Post-Mortem Hippocampus and in Serum from Young, Elder, and Alzheimer’s Patients

Abstract: One of the characteristics of the cerebral aging process is the presence of chronic inflammation through glial cells, which is particularly significant in neurodegeneration. On the other hand, it has been demonstrated that the aryl hydrocarbon receptor (AHR) participates in the inflammatory response. Currently, evidence in animal models shows that the hallmarks of aging are associated with changes in the AHR levels. However, there is no information concerning the behavior and participation of AHR in the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…The indole derivatives were potential ligands of aryl hydrocarbon receptor (AhR) [ 14 ], which is a critical node in linking microbial tryptophan metabolites to brain function [ 63 ], and was involved in neuroinflammation [ 64 ]. In agreement with the findings of enhanced AhR activation in neuropsychiatric disorders of cognitive impairment of AD patients [ 65 ] and depression mice [ 66 ], the enriched indole derivatives were found in our HFHS diet-MDs mice and significantly related with the levels of circulating bile acid TCA and anxiety-like behavior.…”
Section: Discussionsupporting
confidence: 92%
“…The indole derivatives were potential ligands of aryl hydrocarbon receptor (AhR) [ 14 ], which is a critical node in linking microbial tryptophan metabolites to brain function [ 63 ], and was involved in neuroinflammation [ 64 ]. In agreement with the findings of enhanced AhR activation in neuropsychiatric disorders of cognitive impairment of AD patients [ 65 ] and depression mice [ 66 ], the enriched indole derivatives were found in our HFHS diet-MDs mice and significantly related with the levels of circulating bile acid TCA and anxiety-like behavior.…”
Section: Discussionsupporting
confidence: 92%
“…A different relationship has been reported between the AHR and another neurodegenerative disease, Alzheimer's disease (AD). An increase in AHR expression in the astrocytes of aged individuals and AD patients has been observed [92], along with enhanced AHR protein levels in AD patients, while there were no differences between young and old donors. These studies suggest that the AHR is implicated in the aging process of the brain and possibly in the development of AD through its effects on astrocytes.…”
Section: The Ahr and Non-ocular Neurodegenerative Diseasesmentioning
confidence: 87%
“…The effect of AHR-1 on aggregation-prone diseases may suggest novel targeted therapeutic options of relevance for different age-associated diseases. Interestingly, prototype AhR activators, such as TCDD and BaP, were shown to contribute to the development and progression of age-associated diseases (reviewed in [ 62 , 63 ]) in different model systems [ 64 ] and a recent study showed increased AhR levels in serum brains of Alzheimer’s disease patients [ 65 ]. On the other hand, reduced α-synuclein levels were observed in the mouse ventral midbrain upon TCDD-induced AhR-dependent Parkin expression [ 66 ].…”
Section: Discussionmentioning
confidence: 99%